Bad girls don't die - Alender, Katie (New York : Hyperion Books, 2010)
When fifteen-year-old Lexi's younger sister Kasey begins behaving strangely and their old Victorian house seems to take on a life of its own, Lexi investigates and discovers some frightening facts about previous occupants of the house, leading her to believe that many lives are in danger.
Keywords: Demoniac possession -- Juvenile fiction; Haunted houses -- Juvenile fiction; Sisters -- Juvenile fiction; Schools -- Juvenile fiction; Demoniac possession -- Fiction; Haunted houses -- Fiction; Sisters -- Fiction; Schools -- Fiction; Horror stories; Young adult fiction